2019
DOI: 10.20956/jrvi.v3i2.6627
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effect of Golden Snail Powder and Fermented Coconut Cake on Quality of Duck Eggs

Abstract: This study aims to determinate the effect of combination golden snail powder and fermented coconut cake on quality of duck eggs. We were using experimental feeds combination form golden snail powder and fermented coconut cake as raw material for livestock rearing for duck. This research was conducted in July - September 2018 in Mangkoso Village, Barru Regency and continued with sample testing at the Laboratory Animal Husbandry Faculty of Livestock Product Technology University of Hasanuddin. This study used 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Beta carotene is a yellow-orange pigment, which is closely related to egg yolk color (Hien et al, 2016). This result was in line with the result reported by Syaharuddin et al (2019) that the golden apple snail was able to improve the egg yolk color. Galon et al (2017) also reported that cassava leaf meal significantly increased the yolk color.…”
Section: Chemical and Physical Quality Of Eggsupporting
confidence: 93%
See 1 more Smart Citation
“…Beta carotene is a yellow-orange pigment, which is closely related to egg yolk color (Hien et al, 2016). This result was in line with the result reported by Syaharuddin et al (2019) that the golden apple snail was able to improve the egg yolk color. Galon et al (2017) also reported that cassava leaf meal significantly increased the yolk color.…”
Section: Chemical and Physical Quality Of Eggsupporting
confidence: 93%
“…Inclusion of 10% cassava leaf meal in the diet of laying hens (Zanu & Avukpor, 2013), 20% cassava leaf meal in broiler diets (Abu et al, 2015) did not result in any adverse effects on performances. The golden apple snail was reported to be able to improve egg yolk color (Syaharuddin et al, 2019). Galon et al (2017) reported that a diet containing cassava leaf meal improved the egg production.…”
Section: Performances Of Laying Duckmentioning
confidence: 99%